Primary Oral Health Care - Honkala, Eino (Med Princ Pract, 2014)
The aim of this review was to describe the background and evolution of primary oral health care (POHC), including the development of an oral health policy, by identifying the resources necessary for oral health services, reviewing the evidence of the effectiveness of oral health promotion and education, providing essential oral health care, and establishing evidence of the benefits of regular dental visits for effective POHC. At present, evidence for the effectiveness of oral health education and regular dental visits is very weak. Nevertheless, POHC needs to be developed as an integral part of primary health care (PHC). Therefore, a need exists to increase financial investment, resources and workforce in PHC to lower the prevalence of dental caries and periodontal disease in the Middle-East using the POHC approach.